Broadcom´s failed acquisition of qualcomm - offer analysis and company valuation - Both, Kaspar Von (2023)
In November 2017, Broadcom made an initial bid to take over its competitor Qualcomm, a US based semiconductor company, to create one of the largest technology enterprises worldwide in a deal that raised concerns about regulatory approval right from the start. The case examines the situation at the beginning of March 2018 after Broadcom had already made two revised bids and analyzes different angles to give a comprehensive overview of the acquisition. This part of the case study focuses on the valuation of Qualcomm by using multiple approaches to calculate share prices, enterprise, and equity values. Further, it analyzes the different components of the offers made to the target shareholders by highlighting the benefits and shortcomings of the stock and cash payment. Lastly, it discusses the fit of the valuation methodologies taking into consideration the varying business models and approaches.